A COF-based nanoplatform for highly efficient cancer diagnosis, photodynamic therapy and prognosis. Issue 26 (23rd June 2020) - Gao, Peng; Wang, Mengzhen; Chen, Yuanyuan; Pan, Wei; Zhou, Ping; Wan, Xiuyan; Li, Na; Tang, Bo
Abstract : A covalent organic framework-based nanoplatform has been developed for cancer imaging, photodynamic therapy, and prognosis. Abstract : Covalent organic frameworks (COFs) have emerged as a kind of promising material for analytical and biomedical purposes. However, simultaneous cancer diagnosis and therapy with COFs remain a challenge. We report here a COF-based theranostic nanoplatform by integrating a dye-labeled oligonucleotide onto porphyrin-based COF nanoparticles for highly efficient cancer diagnosis and therapy. The fluorescence of the dye was effectively quenched by the COF through fluorescence resonance energy transfer (FRET). In the presence of biomarker survivin mRNA, more stable duplexes were formed and separated from the COF NPs, enabling the recovery of the fluorescence signal and selective cancer imaging. Under NIR laser irradiation, COF NPs generated abundant reactive oxygen species (ROS) to induce cancer cell apoptosis owing to their crystalline reticular structure. In vitro and in vivo experiments revealed that the nanoplatform has a high specificity and inhibition effect toward cancer cells and solid tumors. Interestingly, prognostic evaluation was also realized with COF-survivin. This work will offer new insights into COF-based probes and inspire the development of more versatile tools for biomedical applications.